Application Of Wound Dressing for Skin Integrity Disorders on A Ny S With Diabetic Ulcers in The a RS Iryou Houjin Aiwakai (Ikeda En) Okinawa Japanese Room - Fatimah; Siti Haniyah; Noor Yunida Triana (Viva Medika, 2024)
The prevalence of diabetes in Japan has recently increased, with 11 million adults suffering from diabetes by 2021. The high prevalence of diabetes is associated with a significant economic burden and can be attributed to lifestyle changes and increased longevity. This study aims to evaluate the impact of modern dressing on nursing care for skin integrity disorders at Iryou Houjin Aiwakai Hospital (Ikeda En), Okinawa, Japan. This study used a descriptive method with a case study approach to explore the nursing care process. Data were collected through direct observation, interviews with patients and medical personnel. The results of the study after nursing care for 3 days were that the damage to the skin layer improved, there was still redness and the wound area decreased. This study provides important insights for improving nursing practice and handling patients with diabetic ulcers, and can be a reference in developing more effective care strategies.